Current patterns of menstrual health and hygiene among adolescent and young women of 15-24 years from rural northern India: a community based cross sectional study - Srinath, Kathirvel; Kaur, Ravneet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Menstrual health has an impact on physical, mental and social well-being of young women. Young women in rural areas may face peculiar challenges related to menstrual health and hygiene management (MHHM). In view of evolving lifestyle and behavioural changes in transitional world, there is a need for latest community-based study among young women in rural India. Therefore, we aimed to estimate the magnitude of problems associated with MHHM, and to identify the factors associated with menstrual problems and menstrual hygiene. Methods: House visits were made in the selected villages of Ballabgarh block of Haryana, and 483 non-pregnant women aged 15-24 years were interviewed regarding socio-demographic characteristics and menstrual history (on age of menarche, irregular menstrual bleeding, sanitary pad usage, heavy menstrual bleeding, dysmenorrhea, period fatigue). Dietary diversity was assessed using women dietary diversity (WDD) scale. Multivariable logistic regression analyses were done to identify factors associated with different menstrual problems and strict sanitary pad usage. Results: The prevalences of heavy menstrual bleeding, dysmenorrhea and period fatigue were 20.9%, 26.3%, and 32.0% respectively. Age and marital status were associated with dysmenorrhea. Low dietary diversity was associated with period fatigue. Menarche was delayed among 26.9% and early by 20.8% of the participants. More than nine out of ten participants (92.8%) strictly use sanitary pads. Heavy menstrual bleeding was associated with lesser strict use of sanitary pads. Conclusions: Menstrual problems were common among young women in rural India, and heavy menstrual bleeding was associated with lesser strict use of sanitary pads.